2023
DOI: 10.3390/jof9100965
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress of Piriformospora indica in Improving Plant Growth and Stress Resistance to Plant

Liang Li,
Yu Feng,
Fuyan Qi
et al.

Abstract: Piriformospora indica (Serendipita indica), a mycorrhizal fungus, has garnered significant attention in recent decades owing to its distinctive capacity to stimulate plant growth and augment plant resilience against environmental stressors. As an axenically cultivable fungus, P. indica exhibits a remarkable ability to colonize varieties of plants and promote symbiotic processes by directly influencing nutrient acquisition and hormone metabolism. The interaction of plant and P. indica raises hormone production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 87 publications
0
2
0
Order By: Relevance
“…Fungi are a major group of microorganisms with crucial roles in the natural world. Mycorrhizal and endophytic fungi can enhance plant resistance to diseases and promote plant growth ( Yan et al, 2019 ; Huang et al, 2020 ; Li et al, 2023 ). Wang et al (2023) found that the ectomycorrhizal and saprotrophic communities changed with change in successional stage as the number of years increased by studying changes in functional fungi during forest succession.…”
Section: Introductionmentioning
confidence: 99%
“…Fungi are a major group of microorganisms with crucial roles in the natural world. Mycorrhizal and endophytic fungi can enhance plant resistance to diseases and promote plant growth ( Yan et al, 2019 ; Huang et al, 2020 ; Li et al, 2023 ). Wang et al (2023) found that the ectomycorrhizal and saprotrophic communities changed with change in successional stage as the number of years increased by studying changes in functional fungi during forest succession.…”
Section: Introductionmentioning
confidence: 99%
“…Comparable with arbuscular mycorrhizal fungi (AMF), which are now widely used in plant production, P. indica can form symbiotic relationships with various plants. However, unlike AMF, P. indica has a wider host range and can be isolated and cultured in various synthetic media, which facilitates the in-depth studies of its interaction with plants [ 2 ]. P. indica exhibits a broad spectrum of effects, encompassing not only the stimulation of plant growth and the enhancement of tolerance to both biotic and abiotic stresses but also the induction of systemic resistance in plants [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%